Analisis dan Landasan Teologis Kepemimpinan - Rusmini Rusmini (JMiE (Journal of Management in Education), 2022)
Leadership is a divine mandate. Therefore the Quran has a lot to say about this leadership. This article aims to explain the nature of leadership, the requirements to become a leader, as well as the qualifications to become a leader. This discussion becomes important when it is associated with the image of leadership. To solve this problem, it is necessary to see how the support of the Quran provides justification in choosing leaders, the importance of the position of leaders in Islam, and the criteria for good and qualified leaders. This article concludes that the study of the Quran by taking a management approach, especially leadership studies, has long been carried out by management and leadership thinkers. Some experts conclude that leadership is not something special, but is a responsibility, sacrifice, hard work, authority to serve, even a pioneer of action. This research uses a library research method, namely literature study. The results of this research show that whoever becomes a leader, all his energy, enthusiasm, ambition, patience, liking, and direction must be carried out according to the guidance of the Quran.